\(\frac{a+b}{b+c}=\frac{c+d}{d+a}\Rightarrow\left(a+b\right)\left(d+a\right)=\left(b+c\right)\left(c+d\right)\)
<=> ad + a2 + bd + ab = bc + bd + c2 + cd
<=> ad + a2 + bd + ab - bc - bd - c2 - cd = 0
<=> ad + a2 + ab - bc - c2 - cd = 0
<=> ( ad - cd ) + ( a2 - c2 ) + ( ab - bc ) = 0
<=> d( a - c ) + ( a - c )( a + c ) + b( a - c ) = 0
<=> ( a - c )( a + b + c + d ) = 0
<=> \(\orbr{\begin{cases}a-c=0\\a+b+c+d=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}a=c\\a+b+c+d=0\end{cases}\left(đpcm\right)}\)
\(\frac{a+b}{b+c}=\frac{c+d}{d+a}=\frac{a+b+c+d}{a+b+c+d}\)
TH1: \(a+b+c+d=0\Rightarrowđpcm\)
TH2: \(a+b+c+d\ne0\Rightarrow\frac{a+b}{b+c}=\frac{c+d}{d+a}=1\)
\(\Rightarrow a+b=b+c\)
\(\Rightarrow a=c\left(đpcm\right)\)